2020
DOI: 10.3390/ijerph18010053
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Perceived Stress, Burnout Syndrome, and Self-Efficacy in a Group of Polish Air Traffic Controllers and Maritime Navigators: Similarities and Differences

Abstract: Background: This cross-sectional study aimed to assess the level of perceived stress and occupational burnout in groups of Polish maritime navigators and air traffic controllers. The study was part of research into occupational groups regarded as equally emotionally burdened. We tested the usability of a model linking occupational burnout, perceived stress, and seniority. Methods: The set of questionnaires, including the link burnout questionnaire, perceived stress scale—10, and generalized self-efficacy scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Previous research in understanding variability of pilot performance, centred on distinguishing civil from military pilots, and, in civil aviation pilots, it was mainly focussed on selection (Damos, 2003), personality profiling (Hormann and Maschke, 1996) and risk attitudes to prevent errors (Makarowski et al , 2016). Personality profiling has also been attempted by distinguishing pilots from other groups outside aviation (Glicksohn and Naor-Ziv, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research in understanding variability of pilot performance, centred on distinguishing civil from military pilots, and, in civil aviation pilots, it was mainly focussed on selection (Damos, 2003), personality profiling (Hormann and Maschke, 1996) and risk attitudes to prevent errors (Makarowski et al , 2016). Personality profiling has also been attempted by distinguishing pilots from other groups outside aviation (Glicksohn and Naor-Ziv, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In this case, no comparable studies conducted in the discussed occupational group were found. However, in comparison with employees working in other professions involving high emotional burden, the average score was lower, for example over three points lower than the results obtained in the studies conducted on Polish air traffic controllers [ 48 ], almost three points lower than in the case of Polish maritime navigators and nearly two points lower than among Polish professional firefighters [ 25 ]. It is worth mentioning, however, that the three aforementioned occupational groups were dominated by men.…”
Section: Discussionmentioning
confidence: 67%
“…This was observed in the no risk of burnout with an increased sense of disappointment group. The comparison of the obtained data with the results of other occupational groups leads to the conclusion that the levels of perceived stress in the burnout risk group and in the without full-blown pattern of burnout with high inefficacy group were noticeably higher than the level obtained in the study carried out on a group of Polish air traffic controllers and maritime navigators [ 48 ]. These professions are commonly regarded as highly stressful [ 52 ], and, at the same time, requiring particular personal predispositions from candidates which would make them more resistant to stressors.…”
Section: Discussionmentioning
confidence: 99%